Understanding the Use of EduTech in Schools in the Philippines: Recommendations for Effectiveness - Al-Rashiff Hamjilani Mastul; Claze Therese de Vera; Cristina Beltran Jayme (Engineering Science Letter, 2023)
This article focuses on the utilization of educational technology in schools in the Philippines. The aim of the study is to provide recommendations for the effective use of EduTech in schools. The article takes a qualitative approach in presenting the author's perspective and opinion, supported by relevant literature. Educational technology is a phenomenon that is transforming the educational system of every school in the Philippines. However, there are several barriers to the effective implementation of EduTech, such as lack of infrastructure, teacher training, funding, digital divide, resistance to change, and technical difficulties. The article emphasizes the need for comprehensive and well-funded efforts to support the implementation and utilization of EduTech in schools in the Philippines. The study concludes that it is essential to educate teachers on the use of EduTech to ensure its effective implementation. Schools must also have adequate budgetary allocation to accommodate the use of technologies in instruction, and the digital divide between schools must be addressed to ensure that everyone has equal access to educational technology. Administrators should take the lead in promoting the use of EduTech in schools and creating an atmosphere that influences everyone to make use of these materials. By doing so, teachers and learners will be better equipped with the skills and knowledge necessary to thrive in the ever-evolving digital world.